Externalities of Hair Industry within Nucleus-Plasma Partnership in Purbalingga - Agus Arifin; Rakhmat Priyono (EKO-REGIONAL, 2018)
The aim of this research is to analyze negative externalities of hair industry in Purbalingga Regency. The focus of this research is the effects of hair production activities of nucleous-plasma partnership as part of hair production system. It has been proven that this industry benefits many parts of societies and assists local government program in reducing unemployment and increasing social welfare by labour absorption. However negative externalities have already occured in social and economic views. This research takes samples of 2 factories, 5 plasmas, and 25 workers. The methods using in this research are Dollar-based Ecosystem Valuation Methods. The results show that there are degradation of social interaction among internal family community, reduction of children’s spirit and motivation to achieve high education level, and increasing waste water that endangers to ecosystem.Keywords: Externalities, Haircraft Industry, Nucleus-Plasma, Social Interaction, Waste Water.